Cell density and airspace patterning in the leaf can be manipulated to increase leaf photosynthetic capacity. (15th November 2017) - Lehmeier, Christoph; Pajor, Radoslaw; Lundgren, Marjorie R.; Mathers, Andrew; Sloan, Jen; Bauch, Marion; Mitchell, Alice; Bellasio, Chandra; Green, Adam; Bouyer, Daniel; Schnittger, Arp; Sturrock, Craig; et al.
Summary: The pattern of cell division, growth and separation during leaf development determines the pattern and volume of airspace in a leaf. The resulting balance of cellular material and airspace is expected to significantly influence the primary function of the leaf, photosynthesis, and yet the manner and degree to which cell division patterns affect airspace networks and photosynthesis remains largely unexplored. In this paper we investigate the relationship of cell size and patterning, airspace and photosynthesis by promoting and repressing the expression of cell cycle genes in the leaf mesophyll. Using microCT imaging to quantify leaf cellular architecture and fluorescence/gas exchange analysis to measure leaf function, we show that increased cell density in the mesophyll of Arabidopsis can be used to increase leaf photosynthetic capacity. Our analysis suggests that this occurs both by increasing tissue density (decreasing the relative volume of airspace) and by altering the pattern of airspace distribution within the leaf. Our results indicate that cell division patterns influence the photosynthetic performance of a leaf, and that it is possible to engineer improved photosynthesis via this approach. Significance Statement: The efficiency of photosynthesis is influenced by the distribution of cell material (where photosynthesis occurs) and airspace (by which the carbon dioxide for photosynthesis is delivered), yet the manner and degree to which cell division impacts this balance and, thus, photosynthesis remains largely unexplored. Using a transgenic approach, this paper demonstrates that it is possible to engineer increased photosynthesis by manipulating the patterns of cell division and airspace.